Regulation Reconstruction of Criminal Liability to Political Parties which Practice Money Politics in the Electoral System Based on Dignified Justice - Mhd. Teguh Syuhada Lubis; Teguh Prasetyo; Sri Endah Wahyuningsih (International Journal Reglement & Society (IJRS), 2023)
The regulations about general elections in Indonesia are Act No. 7 of 2017, it was created to address issues in the conduct of elections which are binding on all elements involved in the conduct of elections with the provision of sanctions that can be given to the violators. The application of sanctions includes criminal sanctions (election crime). This regulation does not have any rules regarding criminal liability of political parties which implement money politics and due to the absence of such regulations, the implementation of elections is not based on the concept of elections with integrity and not yet fair and dignified.